2019
DOI: 10.1101/676486
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A gatekeeping function of the replicative polymerase controls pathway choice in the resolution of lesion-stalled replisomes

Abstract: DNA lesions stall the replisome and proper resolution of these obstructions is critical for genome stability.Replisomes can directly replicate past a lesion by error-prone translesion synthesis. Alternatively, replisomes can reprime DNA synthesis downstream of the lesion, creating a single-stranded DNA gap that is repaired primarily in an error-free, homology-directed manner. Here we demonstrate how structural changes within the bacterial replisome determine the resolution pathway of lesion-stalled replisomes.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 106 publications
0
10
0
Order By: Relevance
“…This binding is critical for the gate-keeping function of ε to regulate promiscuous access of β-clamp by Pol IV (Chang et al . 2019 ). Levels of Pol IV would then dictate whether the TLS polymerase gains access to the replisome at the site of the lesion itself or if the replisome would skip the lesion and TLS would then occur behind the replication fork.…”
Section: Mechanisms Of Tls Repairmentioning
confidence: 99%
See 3 more Smart Citations
“…This binding is critical for the gate-keeping function of ε to regulate promiscuous access of β-clamp by Pol IV (Chang et al . 2019 ). Levels of Pol IV would then dictate whether the TLS polymerase gains access to the replisome at the site of the lesion itself or if the replisome would skip the lesion and TLS would then occur behind the replication fork.…”
Section: Mechanisms Of Tls Repairmentioning
confidence: 99%
“…This is supported by a recent study that suggests that the gate-keeping function of ε determines the pathway choice between TLS at and behind the fork (Chang et al . 2019 ).…”
Section: Mechanisms Of Tls Repairmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, TLS may occur 'on-the-fly,' in which a TLS Pol is recruited directly to a stalled replication fork to perform lesion bypass prior to a re-priming event (7). Recent in vitro studies have suggested that this continuous 'on-the-fly' TLS pathway is an early response to replication stalling lesions, whereas re-priming serves as a slower mechanism which is likely utilized during conditions of excessive DNA damage (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%